Safety of recombinant fowlpox strain FP9 and modified vaccinia virus Ankara vaccines against liver-stage P. falciparum malaria in non-immune volunteers. - Webster, D; Dunachie, S; McConkey, S; Poulton, I; Moore, A; Walther, M; Laidlaw, S; Peto, T; Skinner, M; Gilbert, S; Hill, A (2006)
The ability to generate potent antigen-specific T cell responses by vaccination has been a major hurdle in vaccinology. Vaccinia virus and avipox viruses have been shown to be capable of expressing antigens in mammalian cells and can induce a protective immune response against several mammalian pathogens. We report on two such vaccine constructs, modified vaccinia virus Ankara and FP9 (an attenuated fowlpox virus) both expressing the pre-erythrocytic malaria antigen thrombospondin-related adhesion protein and a string of CD8+ epitopes (ME-TRAP). In prime-boost combinations in a mouse model MVA and FP9 are highly immunogenic and induce substantial protective efficacy. A series of human clinical trials using the recombinant MVA and FP9 malaria vaccines encoding ME-TRAP, both independently and in prime-boost combinations with or without the DNA vaccine DNA ME-TRAP, has shown them to be both immunogenic for CD8+ T cells and capable of inducing protective efficacy. We report here a detailed analysis of the safety profiles of these viral vectors and show that anti-vector antibody responses induced by the vectors are generally low to moderate. We conclude that these vectors are safe and show acceptable side effect profiles for prophylactic vaccination.